The impact of Chinese COVID-19 pandemic on the incidence of peripheral facial nerve paralysis after optimizing policies - Yu, Erhui; Jin, Fanyuan; Zhou, Wenhui; Chen, Junkang; Cai, Huafeng; Hu, Jinhua; Xuan, Lihua (Frontiers in Public Health, 2023)
Objective: To evaluate the impact of the COVID-19 pandemic on the occurrence of Peripheral Facial Nerve Palsy (PFNP) in Chinese patients, identify contributing factors, and explore the relationship between COVID-19 and PFNP.Methods: We conducted a retrospective study covering the years 2020 to 2023, categorizing patients into three groups based on their visit dates: Group 1 (December 8, 2020, to February 28, 2021), Group 2 (December 8, 2021, to February 28, 2022), and Group 3 (December 8, 2022, to February 28, 2023). We collected and compared data on disease onset and patient characteristics among these groups.Results: In Group 3, following the widespread COVID-19 outbreak, there was a significant increase of 22.4% and 12.1% in PFNP cases compared to the same periods in the preceding two years (P<0.001). Group 3 patients were more likely to be aged between 30-60 years, experience onset within seven days, present with Hunter syndrome, and have a higher H-B grade of VI compared to the previous two years (P<0.017). Logistic regression analysis revealed a strong association between the COVID-19 pandemic and the incidence of Hunter syndrome in PFNP (OR=3.30, 95% CI 1.81-6.03, P<0.001).Conclusion: The incidence of PFNP increased in China after the COVID-19 pandemic, particularly in patients with Hunter syndrome, indicating that COVID-19 infection can trigger and worsen PFNP.